Tanggung Jawab Pengangkut Terkait Ketersediaan Fasilitas Penumpang Di Atas Kapal - Novela Pattipawaej; Merry Tjoanda; Agustina Balik (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Ship passengers as sea carriers, are entitled to legal protection from the transportation company.Purposes of the Research: This writing aims to examine and discuss the responsibilities of the carrier related to the availability of passenger facilities on board the ship and to examine and discuss the role of the Syahbanddar in carrying out the supervisory function at the port. Methods of the Research: The method used is a normative juridical research method using a case approach, a statutory approach and a conceptual approach.Results of the Research: The results obtained from the research, currently the responsibility of the carrier has not been maximized in providing passenger facilities on the ship because the tickets provided exceed the number of seats on the ship so that some passengers do not get comfortable and safe facilities such as seats which are their rights in accordance with the provisions in Law Number 17 of 2008 concerning Shipping Article 40 paragraph (1). Therefore, the carrier must provide a ticket only based on the number of seats on the ship. This is also inseparable from the role of Syahbanddar as a supervisory body because it is deemed not optimal in carrying out its authority so that there are still stowaway passengers and brokers who trigger more cargo than the tickets provided by the carrier. For this reason, Syahbanddar must be proactive in terms of monitoring the sale of passenger tickets so that there is no overload on the ship.